The aesthetics of disease in Lucretius - Rolim de Moura, Alessandro (Romanitas - Revista de Estudos Grecolatinos, 2025)
Review of KAZANTZIDIS, George. Lucretius on disease: the poetics of morbidity in ‘De rerum natura’. Berlin; Boston: Walter de Gruyter, 2021, viii + 211 pp. (Trends in Classics – Supplementary Volumes, 117). 130,00 (hardcover), 21,99 (paperback). ISBN 978-3-11-072265-9.